Langerhans Cell Sarcoma: A Case Report Demonstrating Morphological and Immunophenotypical Variability within a Single Lesion - Rasika Singh; Charles Edward Keen; Christopher Stone; Patrick Sarsfield (Hindawi Limited, 2017)
Langerhans cells are antigen presenting dendritic cells and tumours arising from these are rare. The tumours arising from these dendritic cells are divided into two categories according to a WHO classification: Langerhans cell histiocytosis and Langerhans cell sarcoma. It is the degree of atypia and clinical aggressiveness that distinguishes the two subtypes. Langerhans cell sarcoma (LCS) is a neoplastic proliferation of Langerhans cells which can occur in skin, bone marrow, lymph nodes, spleen, liver, and lung. LCS can present with multiple cutaneous and systemic lesions. We present a case of Langerhans cell sarcoma with a unique morphological appearance and variable immunohistochemical profile within a single cutaneous lesion. LCS is a rare malignancy and its diagnosis is based on morphology, immunophenotypical examination, and ultrastructural analysis by electron microscopy. Our case highlights a unique morphological description of LCS wherein the pleomorphic neoplastic cells show epidermotropism and are surrounded by a variable amount of inflammatory infiltrate within a single cutaneous lesion. A single cutaneous lesion of Langerhans cell sarcoma with variable immunohistochemical profile has not been described so far.